The VNTR polymorphism of the endothelial nitric oxide synthase gene and blood pressure in women at the end of pregnancy - Evgeny Reshetnikov; Irina Ponomarenko; Oleg Golovchenko; Inna Sorokina; Irina Batlutskaya; Tatyana Yakunchenko; Volodymyr Dvornyk; Alexey Polonikov; Mikhail Churnosov (Elsevier, 2019)
Objective: Examine the association of the 4a/4b polymorphism of endothelial nitric oxide synthase (eNOS) with blood pressure in women at late pregnancy. Materials and methods: Blood pressure before pregnancy and at the end of gestation (37-40-week term) was measured in 588 women of the Russian ancestry. The women were divided into groups according to the body mass index and the presence of preeclampsia at late pregnancy. The 4a/4b polymorphism of the eNOS gene was genotyped using PCR with subsequent screening of amplified fragment length polymorphisms. Results: The 4a4a eNOS genotype was associated with higher levels of diastolic blood pressure in pregnant women and with more pronounced dynamics of the diastolic and mean arterial pressure in the development of pregnancy (p = 0.02-0.03). Pregnant women with the 4a4a genotype and increased body mass index had higher systolic, diastolic, and mean arterial pressure (p = 0.001-0.009). In pregnant women with preeclampsia, the 4a4a genotype was associated with higher level of diastolic blood pressure at the end of pregnancy (p = 0.04), whereas in the women without preeclampsia this genotype was associated with more pronounced changes of blood pressure at pregnancy (p = 0.02). Conclusion: The results of our study suggest that the genotype 4a4a of the eNOS gene is associated with higher levels of blood pressure in women at the end of pregnancy. Keywords: Pregnancy hypertension, Preeclampsia, Endothelial nitric oxide synthase, Gene polymorphism